2019
DOI: 10.1177/1934578x19871404
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Constituents of Branches, Berries, and Leaves of Hippophae rhamnoides L. by UHPLC-ESI-QTOF-MS and Their Anti-Inflammatory Activities

Abstract: Sea buckthorn ( Hippophae rhamnoides L.) is a medicinal plant widely distributed in Asia and Europe, containing plentiful bioactive substances. Our research aimed to promote the comprehensive utilization of the branches, leaves, and berries of sea buckthorn. Qualitative analysis of chemical constituents in branches, leaves, and berries of sea buckthorn was conducted by ultra-high performance liquid chromatography accurate mass quadrupole time-of-flight mass spectrometry with electrospray ionization (UHPLC-ESI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…In vitro and in vivo studies have confirmed the anti-inflammatory, antitumor, hepatoprotective, immunomodulatory, anti-atherogenic, anti-stress, hepatoprotective, radioprotective, tissue repair, antibacterial, antifungal, antiviral, and antioxidant activities, which are determined by the multichemical origin compounds [ 4 , 9 , 10 , 11 , 12 , 13 ]. Fruits and leaves contain rich profiles of carotenoids, tocopherols, amino acids, triterpenic compounds, and phenolic compounds [ 3 , 5 , 7 , 8 , 10 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The phenolic compounds determine the pharmacological effects that are associated with the antioxidant activity [ 10 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo studies have confirmed the anti-inflammatory, antitumor, hepatoprotective, immunomodulatory, anti-atherogenic, anti-stress, hepatoprotective, radioprotective, tissue repair, antibacterial, antifungal, antiviral, and antioxidant activities, which are determined by the multichemical origin compounds [ 4 , 9 , 10 , 11 , 12 , 13 ]. Fruits and leaves contain rich profiles of carotenoids, tocopherols, amino acids, triterpenic compounds, and phenolic compounds [ 3 , 5 , 7 , 8 , 10 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The phenolic compounds determine the pharmacological effects that are associated with the antioxidant activity [ 10 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…leaf/leaves, stem/branches, of both plant sexes, as well as the berries and their seeds and peel (pulp-flakes) are rich sources of various valuable phytochemicals (Cenkowski et al, 2006;G orna s, Dwiecki, et al, 2016;Gradt et al, 2017;Michel et al, 2012;Yang & Kallio, 2002). It has been reported that the bioactive compounds contained in the sea buckthorn possess many biological activities such as antioxidant and anti-enzymatic (Tkacz et al, 2019), anti-inflammatory (Zheng et al, 2019), antitumoral, and anticancer (Masoodi et al, 2020) properties. It has also been claimed that sea buckthorn berries are a promising source of probiotic bacteria, such as Lactobacillus rhamnosus and Ehstreptococcus thermophilus, of which inhibit the activation of purine that is used as an energy source by SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Extracts from fruit of different cultivars of SB efficiently inhibited 15-lipoxygenase (Tkacz et al 2019). Similarly, extracts from the fruit, leaves and twigs of SB exerted efficient inhibitory activity against synthesis of NO Á by LPS-induced RAW264.7 mouse macrophages (Zheng et al 2019). In a more detailed study, kaempferol 3 52.3, 18.2, 26.9, 20.6, 25.1, 17.8, 15.0, 23.6, and 12.5 lM, respectively (Yang et al 2013).…”
Section: Anti-inflammatory Activitymentioning
confidence: 84%